Web-based smart LED for saving energy consumption. Issue 1 (May 2021) - Al-Maghribi, F; Al Fayyedh, I; Hernandi, K A; Nugraha, R; Estananto; Abdurohman, M
Abstract: The lighting system takes a dominant part in the building. However, its use is still inefficient because the light provided by the lamp exceeds its needs and often the light stays on when it is not needed. It can be done by creating a lighting system that provide appropriate light for saving the use of energy. A smart lighting system is designed to control light intensity by using a device that is able to detect light intensity and movement. The lighting system will turn on when there is activity in the room, then the system will adjust the intensity in the room. Also, the energy consumption will be saved in the database to ease monitoring process. By using this system, working room's light intensity will be maintained at standard light intensity value. And also, this system will save power consumption 50.7%.